Relationship between tympanic membrane perforation and conductive hearing loss in patients with chronic otitis media - Ali, Amjed H.; Alshareda, Isam M. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Study performed to evaluate relationship between surface area of tympanic membrane perforation and degree of hearing loss and the effect of perforation site on that relationship in patients with chronic otitis media. Methods: Seventy-five perforated tympanic membranes from 63 patients aged between 14-45 years with inactive mucosal chronic otitis media included in this study. Rigid endoscope (0 degree) used to take an image for each perforation that analyzed by Autodesk Design Review 2013 program. Degree of hearing loss assessed by pure tone audiometry. Surface area of perforation classified into four groups according to its percentage. Perforation site categorized into three groups regarding its relation to handle of malleus. Data analysis carried out with SPSS program version 17. Results: We studied 34 females and 29 males with different surface area and site of perforations. It observed that with increment of surface area of tympanic membrane perforation, the degree of conductive hearing loss increases (P value=0.000). This relationship expressed in a logarithmic equation. The mean hearing loss of posterior perforation was 1.7±0.5 dB for each 1% of perforation but in anterior perforation was 1.5±0.6 dB for each 1% of perforation (p value 0.185). Conclusions: In chronic otitis media, there is a quantitative logarithmic relationship between surface area of tympanic membrane perforation and degree of conductive hearing loss. The site of perforation does not play a significant role in determining degree of conductive hearing loss.